Trade Creation and Diversion in Overlapping ASEAN+6 Agreements - Narandu, Gandri; Sriyanto, Agus (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study provides a unified, directly comparable evaluation of six overlapping ASEAN+6 trade agreements within a single structural gravity framework, thereby overcoming the fragmentation of earlier studies that typically focused on individual agreements, specific commodities, or highly aggregated trade flows. Research Objectives: This study examines whether overlapping trade agreements are associated with trade creation and trade diversion at the regional level and in Indonesia’s bilateral trade across aggregate and sectoral dimensions. Research Methods: Using panel data for 1993–2020, the study applies a structural gravity model estimated with Poisson pseudo-maximum likelihood and fixed effects to address zero trade flows, heteroskedasticity, and unobserved bilateral heterogeneity. Empirical Results: Trade effects differ substantially across agreements. At the regional level, ACFTA and AKFTA exhibit the strongest intra-bloc trade creation, whereas AIFTA, AANZFTA, and AJCEP produce weaker or negative effects. For Indonesia, AKFTA is associated with the most consistent positive export and import performance, while sectoral gains are more concentrated in manufacturing than in primary products. Implications: Overlapping trade agreements should be treated as differentiated policy instruments. Their benefits depend on industrial capability, effective utilization of preferences, harmonized rules of origin, and lower non-tariff barriers. JEL Classification: F14, F15, C23